(Ir)responsible corporations, AI, and the environment : environmental harms in the light of posthumanist theory - Bonde, Jessica (My University, 2023)
In the past few years, great advances in the field of artificial intelligence have been made, bringing about rapid socio-technical change. Positive progress in various areas has been made thanks to it, but there are also downsides to an increased use of technologies such as artificial intelligence. The theoretical framework for the thesis is posthumanist theory, which is an approach that challenges the anthropocentrism that permeates international law. The methodology is based on an interdisciplinary approach and a literary review. The focus of this thesis is how corporations’ use of artificial intelligence is affecting the environment. The primary aim is to examine what responsibilities transnational corporations have in preventing environmental harms when developing and using technologies based on artificial intelligence. The thesis examines transnational corporations as subjects of international environmental law and how they can be held responsible on an international level for environmental harms. Principles of international environmental law provide a framework for international responsibility for corporations. The secondary aim of the thesis is to assess corporations’ obligations to consider environmental impact when developing AI technologies, and this is done through a lens of posthumanist ideas and ideals. Transnational corporations’ role in creating and sustaining environmental harm through accelerating use of technologies such as artificial intelligence should not be ignored, and from the perspective of the legitimacy of international law, it is important to find ways to limit or mitigate the negative effects that their operations have on the environment.

Viime vuosina tekoälyn alalla on tapahtunut merkittävää edistystä, mikä on aiheuttanut nopeita sosioteknisiä muutoksia. Sen ansiosta on saavutettu myönteistä edistystä eri aloilla, mutta teknologioiden, kuten tekoälyn, käytön lisääntymisessä on myös haittapuolia. Tutkielman teoreettinen viitekehys on posthumanistinen teoria, joka haastaa kansainvälisen oikeuden läpäisevän antroposentrismin. Metodologia perustuu monitieteelliseen lähestymistapaan ja kirjallisuuskatsaukseen. Tutkielman painopiste on, miten yritysten tekoälyn käyttö vaikuttaa ympäristöön. Ensisijaisena tavoitteena on tutkia, mikä vastuu monikansallisilla yrityksillä on ympäristöhaittojen ehkäisemisessä kehittäessään ja käyttäessään tekoälyyn perustuvia teknologioita. Tutkielmassa tarkastellaan ylikansallisia yrityksiä kansainvälisen ympäristöoikeuden subjekteina ja sitä, miten ne voidaan saattaa kansainvälisellä tasolla vastuuseen ympäristöhaitoista. Kansainvälisen ympäristöoikeuden periaatteet luovat puitteet yritysten kansainväliselle vastuulle. Tutkielman toissijaisena tavoitteena on arvioida yritysten velvollisuuksia ottaa huomioon ympäristövaikutukset kehittäessään tekoälyteknologioita, ja tämä tehdään posthumanististen ideoiden ja ihanteiden näkökulmasta. Tekoälyn kaltaisten teknologioiden käytön lisääntyessä yritysten roolia ympäristövahinkojen luomisessa ja ylläpitämisessä ei pidä jättää huomiotta - kansainvälisen oikeuden legitimiteetin kannalta olisi tärkeää löytää keinoja rajoittaa tai lieventää niiden toimintojen kielteisiä vaikutuksia ympäristöön.
Keywords: international environmental law, artificial intelligence, environmental harms, corporate responsibility, kansainvälinen ympäristöoikeus, tekoäly, ympäristöhaitat, yritysvastuu